Pengaruh Nilai Aset, Shareholders Equity, dan Total Liabilities terhadap Kinerja Keuangan yang Dimediasi Nilai Kontrak pada Perusahaan Real Estate yang Listing di BEI - Tuhardjo Tuhardjo (Jurnal Aplikasi Manajemen, 2010)
This capital market research attempts to explicate the influence of asset value towards contract value, shareholder equity towards contract value, total liabilities towards contract value, and contract value towards financial performance. The collected data analyzed by using PATH analysis The results finding were: asset value variable significantly influenced contract value, total liabilities being annulled from data analysis because of causing high multicollinearity. Shareholder equity found to be significantly influenced contract value, and contract value found to be significantly influenced financial performance.